Do You Like Online Shopping? A Case Study Courier Service Quality and Customer Satisfaction Between Malaysia, Indonesia, and India - Pei Qi Chew; Le Cheong; Zhi Ying Chin; Zhi Hao Chen; Fathika Medinna Giantoni; Muhammad Asyraf Aditya; Dhruv Panchal; Sk Abdul Nayeem (International Journal of Accounting and Finance in Asia Pasific (IJAFAP), 2024)
The surge in online shopping has led to a growing demand for courier services, making it crucial to understand how service quality impacts customer satisfaction. This study aims to evaluate the effect of five key service quality dimensions—tangibility, reliability, responsiveness, assurance, and empathy—on customer satisfaction in the courier industry across Malaysia, India, and Indonesia. An online survey was conducted with 150 respondents from Universiti Sains Malaysia (USM), Universitas Brawijaya, Indonesia, CMS Business School, India, and IMS Engineering School, India. Regression analysis revealed that only empathy had a significant positive relationship with customer satisfaction, while tangibility, reliability, responsiveness, and assurance did not show significant impacts. These findings suggest that courier companies should focus on improving empathy in their customer service interactions to enhance satisfaction. Understanding and addressing customer needs through personalized service can lead to higher satisfaction and loyalty. This study contributes to the literature on service quality in the courier industry, particularly in the context of online shopping across multiple countries.